A phase I weekly dosing study of brentuximab vedotin in patients with relapsed/refractory CD30-positive hematologic malignancies - Fanale, Michelle A; Forero-Torres, Andres; Rosenblatt, Joseph D; Advani, Ranjana H; Franklin, Anna R; Kennedy, Dana A; Han, Tae H; Sievers, Eric L; Bartlett, Nancy L (Clinical cancer research, 2012)
The antibody-drug conjugate (ADC) brentuximab vedotin comprises a CD30-directed antibody covalently attached to the potent antimicrotubule agent monomethyl auristatin E (MMAE) via a protease-cleavable linker. This study explored the safety, maximum-tolerated dose (MTD), and activity of weekly dosing of brentuximab vedotin in patients with relapsed or refractory CD30-positive hematologic malignancies. In this phase I dose-escalation study, brentuximab vedotin was administered intravenously on Days 1, 8, and 15, of each 28-day cycle at doses ranging from 0.4 to 1.4 mg/kg. Forty-four patients were enrolled: 38 with Hodgkin lymphoma, five with systemic anaplastic large cell lymphoma, and one with peripheral T-cell lymphoma not otherwise specified. Doses were escalated in increments of 0.2 mg/kg until dose-limiting toxicity (DLT) was observed. Patients were monitored for antitherapeutic antibodies and pharmacokinetic parameters. Antitumor assessments were carried out every two cycles. The MTD was 1.2 mg/kg. The most common adverse events were peripheral sensory neuropathy, fatigue, nausea, diarrhea, arthralgia, and pyrexia; and the majority of events were mild to moderate in severity. Tumor regression occurred in 85% of patients and the overall objective response rate was 59% (n = 24), with 34% (n = 14) complete remissions. The median duration of response was not reached at a median follow-up of 45 weeks on study. Weekly administration of brentuximab vedotin resulted in tumor regression and durable remissions in patients with CD30-positive malignancies. This ADC was associated with manageable toxicity, including peripheral neuropathy. Further study in CD30-positive malignancies is warranted.